2019
DOI: 10.1161/strokeaha.119.024843
|View full text |Cite|
|
Sign up to set email alerts
|

Cerebellar Microbleed Distribution Patterns and Cerebral Amyloid Angiopathy

Abstract: Background and purposes: Hematoma location within the cerebellum may help identify the dominant small vessel disease (SVD) type (cerebral amyloid angiopathy [CAA] vs. non-amyloid SVD). However, it is unknown whether this holds true for cerebellar microbleeds (CMBs). We tested the hypothesis that cerebellar CMBs restricted to the cortex and vermis (defined as superficial regions) are associated with clinically diagnosed and pathology-verified CAA. Methods: Three hundred and seven consecutive spontaneous intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 27 publications
(39 reference statements)
4
29
1
1
Order By: Relevance
“…This is along the same line with cerebellar dentate nucleus involvement. As equivalents of deep CMBs, CMBs in cerebellar dentate nucleus are likely due to hypertensive angiopathy as reported in recent studies 18 , 19 . Our prediction models suggested optimal cut-off values of lobar CMBs predicting Aβ positivity as 16.4 (GBM) or 14.3 (RF).…”
Section: Discussionsupporting
confidence: 56%
“…This is along the same line with cerebellar dentate nucleus involvement. As equivalents of deep CMBs, CMBs in cerebellar dentate nucleus are likely due to hypertensive angiopathy as reported in recent studies 18 , 19 . Our prediction models suggested optimal cut-off values of lobar CMBs predicting Aβ positivity as 16.4 (GBM) or 14.3 (RF).…”
Section: Discussionsupporting
confidence: 56%
“…2 ) [ 54 57 ]. Arteriolosclerosis has been found to more commonly present with deep cerebral and cerebellar microbleeds (CMB) [ 56 ], deep lacunes [ 57 ], perivascular spaces (PVS) visible in the basal ganglia [ 55 ], deep ICH and peri-basal ganglia WMH [ 54 ] (Fig. 1 c, Fig.…”
Section: Neuroimaging Evaluationmentioning
confidence: 99%
“…2 ). In contrast, evidence suggests that CAA more typically presents with cortical CMB [ 53 , 56 ], cortical cerebral microinfarcts (CMI) [ 58 ], lobar lacunes [ 57 ], PVS visible in the centrum semiovale [ 55 ], cortical superficial siderosis (cSS) [ 51 ], convexity subarachnoid hemorrhage (cSAH) [ 59 , 60 ], lobar ICH and WMH foci distributed as multiple subcortical spots [ 54 ] (Fig. 1 c, Fig.…”
Section: Neuroimaging Evaluationmentioning
confidence: 99%
“…8 In older populations, the presence of CMBs is associated with increased rates of dementia and vascular events. 9,10 CMBs are also characteristically identified and associated with cognitive impairment in specific disease conditions; for example, cerebral amyloid angiopathy 11 and traumatic diffuse axonal brain injury 12 and as a long-term effect of cranial radiotherapy. 13,14 Only 1 previous published study has explored CMBs in ITP, where a CMB was identified on gradient echo T2* MRI in 1 of 27 children with short duration of ITP.…”
Section: Introductionmentioning
confidence: 99%